Extensive human‐mediated jump dispersal within and across the native and introduced ranges of the invasive termite Reticulitermes flavipes. Issue 16 (1st July 2021) - Eyer, Pierre‐André; Blumenfeld, Alexander J.; Johnson, Laura N. L.; Perdereau, Elfie; Shults, Phillip; Wang, Shichen; Dedeine, Franck; Dupont, Simon; Bagnères, Anne‐Geneviève; Vargo, Edward L.
Abstract: As native ranges are often geographically structured, invasive species originating from a single source population only carry a fraction of the genetic diversity present in their native range. The invasion process is thus often associated with a drastic loss of genetic diversity resulting from a founder event. However, the fraction of diversity brought to the invasive range may vary under different invasion histories, increasing with the size of the propagule, the number of reintroduction events, and/or the total genetic diversity represented by the various source populations in a multiple‐introduction scenario. In this study, we generated a SNP data set for the invasive termite Reticulitermes flavipes from 23 native populations in the eastern United States and six introduced populations throughout the world. Using population genetic analyses and approximate Bayesian computation random forest, we investigated its worldwide invasion history. We found a complex invasion pathway with multiple events out of the native range and bridgehead introductions from the introduced population in France. Our data suggest that extensive long‐distance jump dispersal appears common in both the native and introduced ranges of this species, probably through human transportation. Overall, our results show that similar to multiple introduction events into the invasive range, admixture in the native range prior to invasion can potentially favour invasion success by increasing the genetic diversity that is later transferred to the introduced range.